To Talk or Not to Talk: When Analysts with Social Ties to Firm Managers Acquire Bad News - He, Kaigang; Li, Zengquan; Yang, Yong George; Zhang, Ivy Xiying (The Accounting Review, 2025)
ABSTRACT We study whether sell-side financial analysts’ social ties to firm management help them discern firms’ financial reporting frauds and, upon such detection, how the connected analysts disseminate the information. Using unique data from China, we find that, although unconnected analysts do not manifest a significant change in their likelihood of covering the fraud firms nor in issuing more downgrade stock ratings, connected analysts are significantly more likely to drop coverage right after these firms’ first annual reports containing fraudulent information. Meanwhile, mutual funds with a trading commission relationship to these connected analysts (i.e., client funds) are significantly more likely to unload their holdings of fraud firms than nonclient funds after these firms’ first fraudulent annual reports. Overall, the evidence suggests that analysts with social ties to firm management have early access to bad news and choose to privately communicate the negative information to their clients. Data Availability: All data used in this article are publicly available.